Das Konzept des sozialen Friedens und seine Widersprüche: ein Beitrag zu Aristoteles’ argumentativer und historischer Glaubwürdigkeit - Dietze-Mager, Gertrud (Histos, 2021)
The present article studies Aristotle’s concept of social peace which presupposes a stable politeia based on homonoia between rich and poor, and the existence of a broad middle class. It discusses Aristotle’s analysis of these prerequisites and their disruption by the demagogues and the payments for public service to the polloi. In the process we discover serious contradictions which weaken Aristotle’s reasoning. In the light of external sources it also becomes evident that his information concerning important aspects is misleading, and that, furthermore, he seems to circumvent information which might weaken his attack on what he considers the radical democracy of his time. As a consequence, Aristotle’s reliability as a historical witness is questioned.